Assessment methodology of management personnel - Yunussov, M.B.; Yessirkepova , А.М. (BUKETOV BUSINESS REVIEW, 2019)
The article examines the issue of forming a methodology for evaluating management personnel from the standpoint of the impact of managers' efforts on the results of an organization’s activities, and also a comparative description of assessment methods of management personnel is conducted. It is shown that the degree of objectivity of personnel evaluation directly depends on the actions of the head. Therefore, special emphasis is placed on the ability of the manager to influence the outcomes of the organization, as well as on the team’s ability to influence the evaluation criteria of the management team. Particular attention was paid to the possibility of developing an innovative methodology for evaluating management personnel based on the results of the analysis of the work of the enterprise. The proposed methodology for assessing the effectiveness of management personnel is based on a combination of various methods, taking into account the specifics of the industry, as well as modern requirements for management personnel. The main goal of developing the methodology for evaluating the performance of management personnel is to identify criteria, the application of which in practice will improve the quality of management’s work. Creating an effective system of management capacity is the basis for further development, as well as the achievement of goals. Evaluation of managers at both the middle and top level should be based on assessment procedures, certain technologies and methods. The proposed methodology for assessing the effectiveness of management personnel is based on a combination of various methods, taking into account the specifics of the industry, as well as modern requirements for management personnel.